Marketing Problems of Women Handy-Craft Producers in Jaffna District - Kavitha, S.; Shivany, S. (Sairam Institute of Management Studies, Sai Ram Engineering College., 2020)
The critical challenges in eradicating poverty to meet sustainable incomes, as the number of women‘livelihoods are at lifeless stage. Therefore, government and other related authorities need to set out critical measures to ensure that low income or marginalized groups for instance womenhandicraft producers to meet their basic need via sustainable income through their livelihoods. Due to 30 years of prolonged war, many traditional livelihood activities had been transformed as handicraft works. Post- war technology applications and the intention toward peace and back to normal life, many widows affected by war, selected handicraft as their choice to generate income for their day to day life. Even the but still they face many difficulties, to withstand these livelihoods. Even though these handcraft producers have many potentials in future, few researches tried to explore these likelihoods, and failed to consult them through application-oriented researches. This study used case study as qualitative methodology, to explore their marketing problems. Purposive sampling method was used to collect primary data from 20 female women handicraft producers in Jaffna. through in-depth interviews. This study identified marketing problems of women handicraft producers asinadequate market infrastructure facilities, high raw material prices, lack of marketing facilities, lack of formal loan facilities, inadequate training on market sustainability, high marketing and distribution cost, lack of knowledge about latest designs, existing market demand and facing difficulties to reach large audiences, lack of knowledge in promotional methods and pricing strategies. The study suggested to the handicraft promoting organizations in Jaffna districts to train these producers for their capacity development, and supports should be given to adopt case specific strategies for enlightening their livelihoods as handicraft making.
Keywords: Sustainable; Livelihood; Handicraft producers; Jaffna.